About electron energy increase in discharge with the non-sinusoidal field - Ostroushko, V. (Вопросы атомной науки и техники, 2013)
It is shown that the energy of electrons increases in the case of nonzero value of power spectral density at resonant frequencies irrespective of field strength jumps presence or absence. It is noted the inevitability of the collisional heating and its considerable contribution to the development of ionization. Показано, что энергия электронов увеличивается при ненулевом значении спектральной плотности мощности на резонансных частотах, независимо от присутствия или отсутствия скачков напряженности поля. Указано на неизбежность столкновительного нагрева и его значительный вклад в развитие ионизации. Показано, що енергія електронів збільшується при ненульовому значенні спектральної густини потужності на резонансних частотах, незалежно від присутності або відсутності стрибків напруженості поля. Вказано на неминучість зіткненного нагрівання та його значний внесок у розвиток іонізації.